(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
A simple and rapid UV spectrophotometric method was developed for quantification of remdesivir in bulk and its dosage form which was used in the treatment of COVID 19. Analytical Quality by Design (AQbD) approach was implemented for method development and the relationship between variable input parameters and the method performance characteristics were designed into Ishikawa diagram. The critical parameters were optimized for solvent, wavelength, scan speed and sampling interval, determined by using principal component analysis as well as by observation. The present method was validated according to ICH Q2 (R1) guideline. The method was found excellent linear (r2 ≥ 0.999) at concentration range of 2 -12 μg/mL at maximum wavelength of 245.5 nm. The detection limit and quantitation limit were satisfactorily found to sensitive and precise. The intraday and interday precision were achieved consistent and percentage relative standard deviation (% RSD) were found ≤ 2%. The overall results of forced degradation studies such as acidic, basic, oxidative, thermal and photolytic conditions imply that the developed method could be well implemented as a stability indicating method for the estimation of remdesivir. The result confirmed that the method can be useful for the routine quality control of remdesivir in their pharmaceutical formulations.